Kontribusi Apersepsi dalam Meningkatkan Pemahaman Pada Mata Pelajaran Pendidikan Agama Islam - Zamroji, Muhammad (Tarsib: Jurnal Program Studi PGMI, 2024)
Islamic religious education has an important role in growing and increasing faith, noble character and practicing the teachings of the Islamic religion. The role of teachers is also very large in achieving success in the teaching and learning process. Apperception needs to be done to find out students' knowledge, motivate students by presenting interesting material and encourage students to know various new things. Apperception carried out by the teacher can direct students' knowledge towards the learning objectives to be achieved. Reviewing the lessons that have been learned, conveying inspirational stories, providing motivation given to students will greatly influence the level of thinking and students' understanding of the lesson material provided by the teacher. The results of the research conducted by the author can be seen that: 1). Teachers foster students' enthusiasm for learning through several methods such as telling inspirational stories, advice, role models, fun stories, ice breaking and others. The forms of apperception that are applied are checking students' understanding of the subject matter in previous material, relating a phenomenon to the material to be studied, relating the subject matter presented to the context of everyday life so that students can understand the explanation or description of what they have learned. studied. From this understanding, students will realize and try to practice the values ​​of Islamic teachings so that their thinking, acting and behaving are always imbued with Islamic values ​​which will ultimately form a person who is devout and has good moral character.